Upaya Meningkatkan Kemampuan Profesionalisme Guru dalam Melaksanakan Pembelajaran melalui Supervisi Akademik SMA Negeri 3 Metro - Cahyana, Ibnu Bud (STKIP PGRI Bandar Lampung, 2022)
This study aims to improve the professionalism of teachers in learning through academic supervision. Analysis of technical action data in academic supervision was analyzed descriptively comparatively, by comparing the data in the initial conditions, cycle 1, cycle 2 and cycle 3. Tools and data collection by observation, interviews,. The method used is observation, documentation, and ongoing guidance. Results and discussion of improving academic supervision in improving teacher professionalism. The pre-cycle pedagogical ability totaled 396.9 (65.98%), in the first cycle it increased to 462.5 (77.08%), the second cycle got an average score of 83.32%, and the third cycle got an average score 97.92%. The teacher's professional ability in the first cycle was 68% on average, the second cycle was 91.68% on average, and the third cycle increased to 125.69%.